2013
DOI: 10.1155/2013/289328
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Visible Light Photocatalysis in N-Doped Anatase TiO2with Oxygen Vacancies from GGA+U Calculations

Abstract: We have systematically studied the photocatalytic mechanisms of nitrogen doping in anatase TiO 2 using first-principles calculations based on density functional theory, employing Hubbard U (8.47 eV) on-site correction. The impurity formation energy, charge density, and electronic structure properties of TiO 2 supercells containing substitutional nitrogen, interstitial nitrogen, or oxygen vacancies were evaluated to clarify the mechanisms under visible light. According to the formation energy, a substitutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…A signicant increase of light absorption at lower photon energy levels was observed for all the doped TiO 2 samples, extending the absorption coverage towards 400-550 nm of the visible light region. Furthermore, the work done by H. Wu et al 46 suggests that the formation of oxygen vacancies in the presence of nitrogen is easier as compared to naked TiO 2 . This claim is further supported by the work of Xiang et al, 25 where from rst principle density functional theory (DFT) calculations, an interstitial Nprecursor can induce local states above the valence band and is responsible for the visible light response.…”
Section: Resultsmentioning
confidence: 99%
“…A signicant increase of light absorption at lower photon energy levels was observed for all the doped TiO 2 samples, extending the absorption coverage towards 400-550 nm of the visible light region. Furthermore, the work done by H. Wu et al 46 suggests that the formation of oxygen vacancies in the presence of nitrogen is easier as compared to naked TiO 2 . This claim is further supported by the work of Xiang et al, 25 where from rst principle density functional theory (DFT) calculations, an interstitial Nprecursor can induce local states above the valence band and is responsible for the visible light response.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with those for pristine TMC, 2.1 ps ( 1 ), 36 ps ( 2 ), and 1288 ps ( 3 ) in Table 2, it is shown that the slower recombination process on NFT-500 corresponds to the hole localized on the N 2 p state in Fig. 7B [37,38]. On the other hand, the efficient charge separation of NFT-500 was observed with the lower photocatalytic efficiency under the UV irradiation compared to that for pristine TMC, suggesting the low yield of hydroxyl radical because of less positive potential of N in the localized midgap state (Fig.…”
Section: Charge Transfer Dynamics and Reaction Mechanism On Doped Tmcmentioning
confidence: 78%
“…We previously used the DFT + U method and the following formalism to describe the exchange and correlation potential [6,24]:…”
Section: Calculation Models and Methodsmentioning
confidence: 99%
“…The DFT + U is a method of correcting the underestimation of the bandgap and involves adding an orbitaldependent term to the DFT potential; it has previously been used to describe the electronic structures of transition-metal oxides [22][23][24][25]. Thus, we used the DFT + U method to more accurately represent the electronic structure and optical properties of N/Si-codoped TiO 2 .…”
Section: Introductionmentioning
confidence: 99%